Horizontal merger analysis with endogenous product range choice - Nisvan Erkal; Lijun Pan (Osaka University, Institute of Social and Economic Research (ISER), 2022)
We consider mergers between multi-product firms in a market with monopolistically competitive fringe of single-product firms. Aggregate product variety is determined by product variety choices of multi-product firms and entry/exit decisions of single-product firms. Mergers can generate marginal cost synergies (affecting marginal cost of quantity) or fixed cost synergies (affecting marginal cost of variety). We show that with marginal cost synergies, consumer welfare decreases whenever aggregate variety increases following a merger. However, with fixed cost synergies, an increase in aggregate variety can indicate that the merger is beneficial. Our results also show high synergies do not necessarily improve consumer welfare.
Keywords: L11; L41; D43; 330; Antitrust policy; merger analysis; multiproduct firms; product range choice; entry; cost synergies